Crystallization of the avian reovirus double-stranded RNA-binding and core protein σA - Hermo-Parrado, X. Lois (International Union of Crystallography, 2007)
The avian reovirus protein σA plays a dual role: it is a structural protein forming part of the transcriptionally active core, but it has also been implicated in the resistance of the virus to interferon by strongly binding double-stranded RNA and thus inhibiting the double-stranded RNA-dependent protein kinase. The σA protein has been crystallized from solutions containing ammonium sulfate at pH values around 6. Crystals belonging to space group P1, with unit-cell parameters a = 103.2, b = 129.9, c = 144.0 Å, α = 93.8, β = 105.1, γ = 98.2° were grown and a complete data set has been collected to 2.3 Å resolution. The self-rotation function suggests that σA may form symmetric arrangements in the crystals.